Gender and life-cycle differentials in the impact of schooling on chronic disease in Jamaica - Handa, Sudhanshu (International Food Policy Research Institute, 1997)
The incidence and correlates of adult health are becoming a policy issue in many middle-income countries due to the aging of population structures associated with medical technology and the demographic transition. Adult health problems such as physical disability and non-communicable chronic diseases require unique health infrastructure and expertise and can impose a large cost on already cash-strapped health services. This paper explores the socioeconomic determinants of chronic illness in Jamaica, a middle-income country where chronic diseases are the primary source of the nation’s disease burden. Econometric results from a national household survey indicate that additional education significantly reduces the reporting incidence of chronic illness, with the impact, especially strong among adults aged 14-49. Moreover, this relationship persists after controlling for household resources, suggesting even greater health related social benefits to education than previously considered. Finally, as in other parts of the world and for other health measures, Jamaican women report earlier and higher incidences of chronic illness, but these differences cannot be explained by differences in the level or impact of education, nor are they likely to reflect mortality selection.